Mengurai Permasalahan pada Irigasi Pertanian di Desa Parungsari Kecamatan Wanasalam - Lebak Banten - Ewing Yuvisa Ibrani; Haniyah Haniyah; Sabas Setyohadi; Yenny Dwi Handayani (Universitas Indraprasta PGRI, 2023)
During the second planting season, farmers in Parungsari Lebak Banten Village often complained about their rice fields not having water because there was no rain. This activity of community service aims to analyze the problems that occur in agricultural irrigation in Parungsari Village, , Lebak Regency, Banten. The method used is descriptive with a direct interview and survey approach. The results of this activity indicate that the problems that occur in agricultural irrigation in Parungsari Village, Lebak Regency, Banten include; (1) the flow of water from the main irrigation does not reach Parungsari Village, (2) The lack of a budget for irrigation repair funds from the government, and (3) Rainfed irrigation in Parungsari Village does not guarantee. From these problems, it is hoped that the government will make moves regarding the solutions that will be carried out.